Ավետիք Իսահակյանը աֆորիզմների վարպետ - Մկրտչյան, Նունե (Արմավ հրատ.)
There are few writers in the world literature who, through their aphorisms, would be able to penetrate into the deep layers of the psyche and consciousness of the people and present the philosophical results of their creative work and worldview, thereby turning aphorisms into an inseparable part of thought and speech. Aphorism is a rare genre in the Armenian literature, it is almost not studied. Av. Isahakyan a philosopher, a poet and a writer, was one of the rare writers, whose thinking was inherent in aphorism. Moreover, the Master is an exception: “not a single Armenian writer created so many aphorisms.” The purpose of our study is to present the theme of aphorisms of Avetik Isahakyan: from the native land to the Cosmos, from the history to the reality, from an illusion of the past to a dream of the future - which discusses the themes of the native language and folklore, the Armenian and world literature, art and science, man and nature, life and death, love and suffering. “The first steps of a person’s spiritual development are associated with the poetry, the middle of the path should pass through science and the solution of secrets, and the last steps will again begin with poetry,” Avetik Isahakyan wrote. В мировой литературе мало писателей, которые посредством своих афоризмов сумели бы проникнуть в глубинные пласты психики и сознания народа и представить Исаакян, философ, поэт и писатель, был одним из редких писателей, мышлению которого была присуща афористичность. Более того, Мастер являлся исключением: «ни один армянский писатель не сочинил столько афоризмов». Цель нашего исследования — представить тематику афоризмов Aв․ Исаакяна: от родного края до космоса, от истории до реальности, от иллюзии прошлого до мечты о будущем - в которых рассматриваются темы родного языка и фольклора, армянской и мировой литературы, искусства и науки, человека и природы, жизни и смерти, любви и страданий. «Первые шаги духовного развития человека связаны с поэзией, середина пути должна пройти через науку и разгадку тайны, а последние шаги опять начнутся с поэзии», — писал Аветик Исаакян.
Keywords: Գրականություն